Speech acts and language styles of Biden’s victory speech for promoting peace values - Fitri Rahmawati Astiandani; Slamet Setiawan; Ali Mustofa (Studies in English Language and Education, 2022)
The importance of language in expressing ideas and ideologies has always been a focus of public debate in politics. The persons in charge of the reins of power become a source of concern, as well as the language they use. As a result, this research looks into the speech acts, language styles, and how they express peace values from Biden’s victory speech. A qualitative research design was used. Biden’s pragma stylistics and peace values were extracted from his victory speech in Wilmington, Delaware on November 7, 2020. This study focused on three aspects, namely: categories of illocutionary acts, language style based on sentence structure, and peace values. The data were analyzed following these stages: data condensation, data display, and drawing/verifying conclusions. The results showed that the most common illocutionary type employed in diverse language styles in Biden’s victory speech was commissive. Presumably, politicians have become accustomed to making promises or making commitments in order to entice citizens to vote for them. In addition, two types of peace values (inner peace and social peace) were discovered along with three types of language styles: parallelism, antithesis, and repetition (epizeuxis, anaphora, and anadiplosis), with more than half of the data employing parallelism as the language style. The majority of Biden’s speech focused on social peace to keep social life free of internal strife.